Pedagogical Translanguaging - Cenoz, Jasone (Social Sciences, 2021)
This Element looks at the way pedagogical translanguaging can be applied in language and content classes and how it can be valuable for the protection and promotion of minority languages. This title is also available as Open Access on Cambridge Core.